Experimental Study on Influence of Temperature to Control Performance for Viscoelastic Materials Pounding Tuned Mass Damper - Ye, Dehui; Tan, Jie; Liang, Yabin; Feng, Qian (Frontiers in Materials, 2021)
The pounding tuned mass damper (PTMD) is a novel passive damper that absorbs and dissipates energy by an auxiliary tuned spring-mass system. Viscoelastic materials are attached to the interface of the limitation collar in the PTMD so that the energy dissipation capacity can be enhanced. Previous studies have successfully demonstrated the effectiveness of PTMD at room temperature. However, in practice, the PTMD may face a broad temperature range, which can affect the mechanical properties of the viscoelastic materials. Thus, the study of vibration control effectiveness of PTMD at different temperatures is of great significance for its practical engineering application. In this paper, a series of experiments were conducted to investigate the performance of a PTMD in a temperature-controlled environment. A PTMD device was designed to suppress the vibration of a portal frame structure and tested across environmental temperatures ranging from -20℃ to 45℃. The displacement reduction ratios demonstrated the temperature robustness of the PTMD.